Pengaruh Service Quality dan Customer Engagement Terhadap Minat Nasabah untuk Menggunakan Produk PT Bank Central Asia di Jakarta - Ayu Wulandari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purposes of this journal article namely are: 1) To determine the effect of service quality on customer intention to use the products of BCA; and 2) To determine the effect of customer engagement on customer intention to use the products of BCA. This research is a descriptive type with cross sectional method. The data used are primary data obtained from distributing questionnaires directly to the research sample. The study population consisted of all customers conducting transactions at Bank BCA KCP Samanhudi Jakarta. The research sample was determined using the non-probability method with accidental sampling (convenience sampling) technique and obtained a total sample of 175 respondents. The research data were analyzed using multiple linear regression tests.The results of the study stated that service quality has a positive and significant effect on customer interests. The higher the service quality provided by BCA banks, the higher the intention of customers to use the products of BCA. Other results state that customer engagement has a positive and significant effect on customer intention. The higher customer engagement, the higher the customer intention in using BCA products.